Infrastructure investment and economic growth, relevance of institutional factors - Esquivel Monge, Manfred (2018)
We quantify the effect of infrastructure investment on economic growth and test whether that effect is conditioned by institutional factors. This is done by estimating dynamic panel data models with instrumental variables using GMM estimation. Results are in line with those reported by previous studies in terms of the magnitude of the effect of infrastructure on economic growth. Evidence suggests that bad institutions lessen the potential expansive effect of infrastructure investment. Latin American countries would be restraining the expansive potential of their infrastructure investment by showing unfavorable institutional performance. The same would be happening with mid and low-income countries.